Examining the challenges posed to parents by the contemporary screen environments of children: a qualitative investigation - Emma Solomon-Moore; Joe Matthews; Thomas Reid; Zoi Toumpakari; Simon J. Sebire; Janice L. Thompson; Deborah A. Lawlor; Russell Jago (BMC, 2018)
Abstract Background The ubiquity of technology in modern society has led to the American Academy of Pediatrics adapting their screen-viewing (SV) recommendations for children. The revised guidelines encourage families to identify an appropriate balance between SV and other activities. The aims of this study were to explore parents' views of their child's SV time and how important it is for families to achieve a 'digital balance'. Methods Semi-structured telephone interviews were conducted with 51 parents of 8-9-year-old children, between July and October 2016. Inductive and deductive content analyses were used to explore parents' perceptions of their child's level of SV (low, medium, high), how parents feel about child SV, and the importance placed on achieving a digital balance. Parent report of child SV behaviours on weekdays and weekend days were assessed via questionnaire. Results Interview data revealed that because SV is considered the 'norm', parents struggle to limit it, partly because they want their children to be equipped for the modern technological world. While most parents believe SV to have negative effects on children, parents also report advantages to SV. Many parents feel that not all SV is equal, with tablets considered worse than television because of the isolated nature of activities, and educational SV considered more beneficial than non-educational SV. Most parents feel it is important for their family to achieve a digital balance, primarily to spend more quality family time together. Large variation was observed in parents' descriptions of child SV time on weekdays and weekend days. Conclusions Parents recognise the importance of digital balance but want their children to fit into the ever-advancing digital world. Parents do not treat all SV equally. Watching television and engaging in educational SV may be encouraged, while 'playing' on tablets is discouraged. These findings highlight the challenge faced by researchers and policy makers to help families achieve a digital balance, and strategies are needed to support parents to plan child SV time.